Collection Development in the Context of Electronic Publications and Networking: Problems and Prospects - Maheswarappa, B.S.; Tadasad, P.C. (DESIDOC Journal of Library & Information Technology, 2004)
This article critically examines the issues in development of collection for libraries in the context of electronic publication and networking with special reference to formulation of policies, users, formats, storage, mode of access, selection, acquisition, bibliographical control, finance, evaluation,-and manpower. It concludes that developing a need-based, relevant and cost-effective collection, consisting of electronic and other publications in document form, requires systematic planning, and effective implementation. http://dx.doi.org/10.14429/dbit.17.1.8092